2017
DOI: 10.1515/msp-2017-0079
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of mechanical, vibrational and thermodynamic properties of magnetic XC compounds (X = Rb, Sr)

Abstract: Lattice dynamic and mechanical properties of hypothetical RbC and SrC compounds were investigated using the ab-initio pseudopotential method and a linear response scheme. The lattice dynamics was studied in the framework of the density functional perturbation theory (DFPT). The dynamical and mechanical stability of the hypothetical RbC and SrC compounds was proved in their equilibrium B1 structure. In addition, the same stability was confirmed in the B3 phase. The thermodynamic properties were also investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Moreover, elastic and vibrational stability have been confirmed for some binary compounds such as SrC and RbC [20]. According to the paper of Zhang et al [16] and Lakdja et al [20], the SrC compound is found to be a half-metal, whereas the RbC compound is a semiconductor. There was suggested a possibility to have half-metallicity by doping alkali compounds with alkaline earth or vice versa [16].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, elastic and vibrational stability have been confirmed for some binary compounds such as SrC and RbC [20]. According to the paper of Zhang et al [16] and Lakdja et al [20], the SrC compound is found to be a half-metal, whereas the RbC compound is a semiconductor. There was suggested a possibility to have half-metallicity by doping alkali compounds with alkaline earth or vice versa [16].…”
Section: Introductionmentioning
confidence: 95%
“…In particular, carbon-based compounds exhibit ferromagnetism in various structures as binaries [6,9,12,14,16] and also as heusler-type structures [18,19]. Moreover, elastic and vibrational stability have been confirmed for some binary compounds such as SrC and RbC [20]. According to the paper of Zhang et al [16] and Lakdja et al [20], the SrC compound is found to be a half-metal, whereas the RbC compound is a semiconductor.…”
Section: Introductionmentioning
confidence: 98%